The Anterolateral Thigh-Medial Femoral Condyle Chimeric Flow-through Flap for Posttraumatic Wrist Arthrodesis. Issue 3 (September 2019) - Kurlander, David E.; Wu-Fienberg, Yuewei; Long, Tobias C.; Rowe, David J.; Gatherwright, James
Abstract : Wrist arthrodesis in the setting of segmental bone loss can have high failure rates. Therefore, vascularized bone grafting has been advocated for select patients. Patients suffering concomitant large soft tissue loss present even greater challenge. To that end, we describe for the first time successful anterolateral thigh-medial femoral condyle chimeric flow-through flap for posttraumatic wrist arthrodesis and soft tissue coverage. This is a case report of a 19-year-old male laborer who suffered a large blast injury resulting in significant bone and soft tissue injury to the dominant right hand and wrist. After multiple debridements, there was a segmental bone defect from the distal radius and ulna to the metacarpal bases, as well as a 12×8 cm dorsal soft tissue defect. This was reconstructed with a anterolateral thigh-medial femoral condyle chimeric flow-through flap and concomitant wrist arthrodesis in a single stage. Besides a donor site thigh seroma, recovery was uneventful with clinical and radiographic evidence of fusion by >9 weeks postoperation.